Initial study of population and microhabitat of the Banggai cardinalfish (Pterapogon kauderni) in Bilalang Bay, Banggai Regency - Rahman, Samsu Adi; Djiada, Herdiyanto; Suhermanto, Achmad; Safir, Muhammad (Universitas Malikussaleh, 2024)
The Banggai cardinalfish is an endemic fish in Banggai waters which is experiencing a population decline caused by excessive exploitation and degradation of its microhabitat. This research aims to determine the population of the Banggai cardinalfish and its microhabitat in Bilalang Bay. The research was conducted from January to February 2023 in Bilalang Bay, Banggai Regency, Central Sulawesi. Research data collection used the Underwater Visual Survey (UVS) method using a 20mx5m belt transect (2.5m left and right of the transect rope) at five observation stations. Observations made included recruits (<25 mm) Total Length, juveniles (25-60 mm), and adults (>60 mm). The results of observations of the population and density of the Banggai cardinalfish differ based on five observation stations. The highest population of the Banggai cardinalfish is found at location II with a total population of 4,412 fish, consisting of 2,510 adult size fish, 1,800 juvenile size fish, and 102 recruit size fish, with a density of adults 21.1 ind/m2, juvenile density 8 ind/m2, and recruit density 0.5 ind/m2. Meanwhile, the highest population based on size is adult size. The recruitment stage of the Banggai cardinalfish is only found in stations 1, 2, and 3, with microhabitats of sea urchins and anemones. The Banggai cardinal fish has the highest population at station 2.Keywords: Endemic; Banggai cardinalfish; Microhabitat; Population; Bilalang Bay